Myocardial Energy Metabolism in Non-ischemic Cardiomyopathy - Greenwell, Amanda A.; Gopal, Keshav; Ussher, John R. (Frontiers in Physiology, 2020)
As the most metabolically demanding organ in the body, the heart must generate massive amounts of energy (ATP) from the oxidation of fatty acids, carbohydrates and other fuels (e.g. amino acids, ketone bodies), in order to sustain constant contractile function. While the healthy mature heart acts omnivorously and is highly flexible in its ability to utilize the numerous fuel sources delivered to it through its coronary circulation, the heart's ability to produce ATP from these fuel sources becomes perturbed in numerous cardiovascular disorders. This includes ischemic heart disease and myocardial infarction, as well as in various cardiomyopathies that often precede the development of overt heart failure. We herein will provide an overview of myocardial energy metabolism in the healthy heart, while describing the numerous perturbations that take place in various nonischemic cardiomyopathies such as hypertrophic cardiomyopathy, diabetic cardiomyopathy, arrhythmogenic cardiomyopathy, and the cardiomyopathy associated with the rare genetic disease, Barth Syndrome. Based on preclinical evidence where optimizing myocardial energy metabolism has been shown to attenuate cardiac dysfunction, we will discuss the feasibility of myocardial energetics optimization as an approach to treat the cardiac pathology associated with these various nonischemic cardiomyopathies.